Pengaruh Beban Kerja, Stres Kerja, dan Kelelahan Kerja Terhadap Tingkat Turnover Intention Karyawan Pada PT. Capella Multidana Medan - Rini Astuti; Irwan Syari Tanjung; Sya’lum Salsabila (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2023)
The research problem was the number of employees of PT. Capella Multidana Medan stopped working because of her own will due to the high workload, and the amount of work pressure felt which resulted in employee burnout both physically and mentally. Rivai (2019: 240) suggests that several factors can affect employees' desire to stop working (turnover intention), namely: workload, work stress, work fatigue, length of service, work conflict, social support, job satisfaction, compensation, and punishment (punishment). Research purpose to find out how the influence of workload, work stress, and burnout on the level of employee turnover intention at PT. Capella Multidana Medan. This research was the associative- quantitative research. The population in this research was all marketing employees (collectors and surveyors) of PT. Capella Multidana Medan, Jalan Nibung branch, with a total of 40 employees. The number of samples taken was 40 respondents. The side technique used was saturated sampling. The primary data collection method used was a questionnaire method. This research was conducted in 2023. The data analysis technique used was multiple linear regression. Research data processing using the SPSS 24.0 application..